Unifikasi Hukum Nasional Dalam Tindak Pidana Pembunuhan Berlatar Belakang Hukum Adat - Andika Wahyudi Gani; Muhammad Takbir (Fakultas Hukum Universitas Islam Indonesia, 2020)
This research describes the form of unification of national law on legal plurality in Indonesia. This is a case study research conducted in two regions in South Sulawesi, namely Jeneponto and Gowa Regencies. The aim is to investigate the unequal legal relations between positivistic national law and customary law. The methods used Werner Menski socio-legal approach and legislation approach. The results of this study are, first, law enforcers, in this case the Public Prosecutor and the Panel of Judges, in deciding cases only refer entirely to the law while ignoring customary law. On the other hand the defendant believes instead that his actions to be the right actions and should not be regretted based on his customary law. This is because of its position as a community law enforcer. Second, national law stands very dominant from other laws, especially customary law.